Peningkatan Kapasitas Kader Kesehatan dalam Penyelenggaraan Posyandu Integrasi Layanan Primer di Pekon Waringin Sari Timur Kecamatan Adiluwih Kabupaten Pringsewu - Ludiantika Gusrevindo (Lembaga Pengabdian Masyarakat Institut Pemerintahan Dalam Negeri, 2025)
This community service activity aims to enhance the capacity of Posyandu cadres in adapting to the transformation of community-based health services toward the integrated Posyandu model within the Village Community Institution (LKD) as outlined in the Guidelines for Posyandu Management in the Health Sector (Ministry of Health, 2023). This transformation requires cadres to possess technical, managerial, and digital competencies to effectively carry out promotive and preventive functions within the framework of primary health care transformation. The activity employed a Participatory Action Learning (PAL) approach through participatory training, practical simulations, and field reflections conducted in Waringin Sari Timur Village, Adiluwih District, Pringsewu Regency, involving 25 Posyandu cadres and health workers from Bandung Baru Health Center. The results indicated a significant improvement in cadre capacity, with the average pre-test score of 52.3% increasing to 86.5% in the post-test, particularly in digital reporting and institutional understanding of Posyandu. Cadres also showed greater confidence in using digital tools and a deeper understanding of Posyandu’s strategic role as a partner of the village government. This activity demonstrates that participatory and digital-based approaches are effective in strengthening cadre capacity as change agents and as a bridge between national health policies and community-level health practices.